Frequency of Different Child Pug Class Presentation in Patients of Chronic Hepatitis-C and Diabetes Mellitus Based on HBA1c (Medical Forum Monthly, 2024)
Objective: To determine the frequency of different Child Pugh class presentations among patients with chronic hepatitis C and diabetes mellitus and to compare different child pugh class presentations among patients with chronic hepatitis C and diabetes mellitus based on HbA1c.Study Design: Descriptive case series studyPlace and Duration of Study: The study was conducted at the Department of Medicine, Shifa International Hospital, Islamabad in a period of 01 year i.e. from June, 2011 to June, 2012.Materials and Methods: In this study a total of 500 patients with hepatitis C and diabetes mellitus were enrolled. Male and female adult patients, diagnosed with diabetes mellitus and chronic hepatitis C, at least six month history of both diabetes and chronic hepatitis C infection were included in the study. Patients with other causes of chronic hepatitis, like chronic alcoholism, chronic hepatitis B, hemochromatosis, autoimmune hepatitis were excluded from the study.Results: Average age of patients was 59.5 + 14.8 years. Majority of the patients were above 40 years of age. There were 245 (49.0%) males and 255 (51.0%) females. Of the 500 study patients, 189 (37.8%) had child pugh class A, 148 (29.6%) patients had child pugh class B. While 163 (32.6%) patients had child pugh class C. In group 1 (HbA1c < 7%), of the total 307 cases, 107 (37.8%) were in class A, 89 (28.9%) were in class B while 111 (36.2%) were in class C. Similarly, in group 2 (HbA1c > 7%), of the total 193 cases, 82 (42.4%) were in class A, 59 (30.5%) were in class B and 52 (26.9%) were in class C. There was a significant association between child class C and group 1 (HbA1c < 7%) (p-value = 0.04).Conclusion: Based on our results it is concluded that strict glycemic control i.e HbA1c of < 7% has a significant association with adverse outcome i.e child pugh class C in patients with chronic hepatitis C and diabetes mellitus.